ROLE OF VARMAM THERAPY IN KUMBAVATHAM MANAGEMENT - Chelvi ks, Maanickha; Kumar, Rajesh; Kumar A, Rajendra (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Introduction: Siddha medicine, one among the ancient indigenous medical systems of India, has a repository of classical formulations as internal medication and various other unique techniques/therapies as external usage. Varmam is one among such therapies used to treat multiple ailments, especially related to musculoskeletal and neurological deficits. Sometimes, varmam therapy is used along with internal medications and external applications as well. Objective: Adhesive capsulitis or periarthritis may be correlated with kumbavatham which is one of the vatha diseases mentioned in the Siddha literature Yugi Vaithya Chinthamani. Kumbavatham is one of the most common rheumatological problems in old age group, especially those in diabetic participants. It is the most common long-term complication next to osteoarthritis in diabetes mellitus patients. Methods: The present intervention was done in kumbavatham patients who volunteered to undergo the varmam therapy with regular outpatient department medications, and the results were presented. The effect of varmam therapy on kumbavatham was assessed in accordance with shoulder pain and disability index. Result and Conclusion: The result of the current study concludes that the varmam therapy might be useful in the management of kumbavatham diseases and thus improves the quality of life of the patients. Keywords: Kumbavatham, Adhesive capsulitis, Varmam therapy, Diabetes mellitus, Siddha.